THE RELATIONSHIP BETWEEN THE USE OF 3 MONTH INJECTIONS AND IMPLANTS IN WOMEN OF CHILDBEARING AGE TO THE INCREASE IN ACCEPTOR WEIGHT IN PURWODADI 1 - Raisa Melina Anik Ulul Faizah; Wahyu Utami Ekasari; Dewi Sapta Wati (Jurnal Profesi Bidan Indonesia, 2025)
ABSTRACT Background ; The hormone progesterone can facilitate the turnover of carbohydrates and sugar into fat, so that the fat at the base of the skin increases which has an impact on increasing body weight. World Health Organization in 2020 the prevalence of birth control use in the world is injectable birth control users 35.3%, implants 7.3%. According to the BPS in 2021, family planning participants in Indonesia, injectable family planning 66.49%, implants 8.85%. Side effects complained of by 3-month injectable and implantable family planning acceptors related to the contraceptive method used weight gain. Finally, many acceptors choose to drop out. Purpose; This study aims to analyze the relationship between the use of 3 month injection contraception and implant contraception in women of childbearing age and the increase in body weight of acceptors at the Purwodadi Health Center 1. Methods; This research is a quantitative study using a cross section approach. The type of non probability sampling technique is purposive sampling with a sample size of 70. Results; based on SPSS from the mann - whitney test shows a p value of 0.000 3 month injectable birth control and 0.008 implantable birth control. Conclusion; based on the research there is a relationship between the use of 3 month injectable birth control and implantable birth control in women of childbearing age towards increasing acceptor weight at Purwodadi 1 health center.